Populus endo‐glucanase 16 localizes to the cell walls of developing tissues. (30th January 2023) - Behar, Hila; Mottiar, Yaseen; Chandrasekhar, Rohan; Grappadelli, Allegra Corelli; Pauly, Markus; Samuels, A. Lacey; Mansfield, Shawn D.; Brumer, Harry
Abstract: The hemicelluloses comprise a group of matrix glycans that interact with cellulose microfibrils in plant cell walls and play important roles in establishing wall architecture. The structures of hemicelluloses are determined by carbohydrate‐active enzymes (CAZymes) that synthesize, integrate, and break down these polymers. Specifically, endo‐glucanase 16 (EG16) enzymes, which are related to the well‐known xyloglucan endotransglycosylase/hydrolase ( XTH ) gene products in Glycoside Hydrolase Family 16 (GH16), have been implicated in the degradation of the β(1, 4)‐linked backbone of mixed‐linkage β(1, 3);β(1, 4)‐glucans (MLG) and xyloglucans. EG16 members are single‐copy genes found in most plant clades but are absent from many eudicots, including the model plant Arabidopsis thaliana . Until recently, EG16 members had only been characterized in vitro, establishing their substrate specificity, protein structure, and phylogenetic history, but their biological function was unknown. Here we used a hybrid polar, Populus alba × Populus grandidentata (P39), as a model to examine EG16 expression, subcellular localization, and pheno‐ and chemotypes of EG16 ‐downregulated P39 plants. Populus EG16 expression is strong in young tissues, but RNAi‐mediated downregulation did not impact plant growth nor the fine structure of the hemicellulose xyloglucan, suggesting a restricted or currently unknown role in angiosperm physiology.